Economics, information systems, and electronic commerce : empirical research - Kauffman, Robert J.; Tallon, Paul P. (Advances in management information systems ;, 2009)
This groundbreaking volume introduces new methodological approaches to data analysis as well as new techniques for collecting and cataloging transactional data to assist IS researchers in dealing with new and radical forms of IT innovation that continue to energize electronic commerce.